2008
DOI: 10.1016/j.jaut.2007.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous recovery from early glomerular inflammation is associated with resistance to anti-GBM glomerulonephritis: tolerance and autoimmune tissue injury

Abstract: Different susceptibility to anti-GBM glomerulonephritis (GN) among animal strains has been reported. Using our rat model for T cell-mediated anti-GBM GN, this study initiated an investigation on the mechanism related with GN-susceptibility. Anti-GBM GN was induced either though immunization with the nephritogenic T cell epitope pCol(28-40) from Col4α3NC1 or through the transfer of specific T cells. WKY rats were highly susceptible to GN while immuno-compatible LEW rats were GN-resistant. GN-resistance in LEW r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 7 publications
(25 citation statements)
references
References 41 publications
1
24
0
Order By: Relevance
“…1a) [19]. Detailed analyses by immunofluorescence and flow cytometry showed that T cells invaded glomeruli as early as day 15 (fig.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…1a) [19]. Detailed analyses by immunofluorescence and flow cytometry showed that T cells invaded glomeruli as early as day 15 (fig.…”
Section: Resultsmentioning
confidence: 99%
“…Detailed analyses by immunofluorescence and flow cytometry showed that T cells invaded glomeruli as early as day 15 (fig. 1b) [19,20], followed by an influx of both ED1 + macrophage and CD4 + T cells at days 17–20 (fig. 1b).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations